Non-native fish species in the North Aegean Sea: a review of their distributions integrating unpublished fisheries data - Evangelopoulos, Athanasios; Karampetsis, Dimitrios; Christidis, Aris; Gubili, Chrysoula; Sapounidis, Argyrios; Adamidou, Angeliki; Kamidis, Nikolaos; Koutrakis, Emmanouil (Frontiers in Marine Science, 2024)
Fisheries-dependent data and information gathered through fisheries-related scientific surveys can significantly contribute to research on the patterns and processes underlying marine biological invasions and their interactions with fisheries. This study presents an overview of the presence of non-native fish species in the North Aegean Sea, offering insights into their distributions and impact on fisheries. The findings are based on a comprehensive compilation of commercial fisheries-dependent and scientific survey data collected in Greece from 2016 to 2023, along with a systematic review of the international scientific literature. The study resulted in the documentation of the presence of 37 non-native fish species, including several recorded for the first time in the area. The results suggest that non-native fish species invasions in the North Aegean Sea are dynamic. Although most species were classified as casual, and the frequencies of occurrence as well as the quantities in commercial fisheries catches of established species are smaller than in the South Aegean Sea, species introductions and the extent of occurrence and area of occupancy of several species have been increasing since the 2000s. The significance of non-native fish species is becoming increasingly relevant to commercial fisheries in the study area. This is particularly evident in the Northeastern Aegean Sea, where catches of non-native species are on the rise, and new species with potential commercial value have emerged in recent years.